The pacifist Jesus and the violent Jesus in the Gospel of Matthew - Sim, David C. (HTS teologiese studies, 2011)
The Gospel of Matthew presents two starkly different depictions of Jesus. The earthly Jesus of the past is a pacifist who teaches non-violence, compassion, non-retaliation, forgiveness and love of enemies, and he lives his life according to these ideals. The other Jesus is the eschatological figure of judgement who is the antithesis of the earthly Jesus. This Jesus is violent, merciless and vengeful in his treatment of the wicked. The evangelist constructed and promoted this terrible figure of judgement to assist his readers to cope with certain situations of crisis, but in doing so he paid a steep christological price by presenting Jesus in contradictory terms.